Vibratory Creep Feed Grinding - Fujiwara, Junsuke; Hanasaki, Shinsaku; Hasegawa, Yoshio; Wada, Tadahiro (Transactions of the Japan Society of Mechanical Engineers Series C, 1994)
In creep feed grinding, a burn mark is often made on a workpiece. In order to prevent formation of a burn mark, vibratory creep feed grinding is proposed in this study. The workpiece was forced to vibrate in the table feed direction. In vibratory creep feed grinding, the effects of the workpiece vibration on the grinding performance are experimentally investigated. The main results obtained are as follows : ( 1 ) Vibratory creep feed grinding is effective for the prevention of the burn mark. However, the wheel wear in vibratory creep feed grinding becomes larger than that in the conventional method. ( 2 ) In down-cut grinding, more grinding fluid is supplied to the wheel-workpiece contact area in this method than in conventional grinding. However, in up-cut grinding, the amount of grinding fluid supplied does not increase. ( 3 ) Both radial wheel wear and vertical grinding force increase with the increase of the wheel depth of cut under the same metal removal rate.